2017
DOI: 10.1111/hiv.12495
|View full text |Cite
|
Sign up to set email alerts
|

Changes in elevated cholesterol in the era of tenofovir in South Africa: risk factors, clinical management and outcomes

Abstract: Older age, higher BMI, lower CD4 count and a non-tenofovir regimen were risk factors for incident elevated TC. Current guidelines do not indicate regular cholesterol testing at ART clinic visits, which are the main exposure to regular clinical monitoring for most HIV-positive individuals. If regular cholesterol monitoring is conducted, improvements can be made to identify and treat patients sooner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…This is consistent with the results of Ceccato et al [19]; who found that among patients with dyslipidaemia, most individuals had lower CD4 counts (< 200 cells/mm 3 ). A study from a South African population on ART also reported unfavorable lipid profile changes, with lower CD4 count being risk factor for elevated cholesterol [27]. This is; however; in contrast with the previous reports involving patients on ART where lower CD4 count was associated with better lipid profile [15,16,18].…”
Section: Plos Onementioning
confidence: 83%
See 1 more Smart Citation
“…This is consistent with the results of Ceccato et al [19]; who found that among patients with dyslipidaemia, most individuals had lower CD4 counts (< 200 cells/mm 3 ). A study from a South African population on ART also reported unfavorable lipid profile changes, with lower CD4 count being risk factor for elevated cholesterol [27]. This is; however; in contrast with the previous reports involving patients on ART where lower CD4 count was associated with better lipid profile [15,16,18].…”
Section: Plos Onementioning
confidence: 83%
“…However, the Brazilian study found higher prevalence rate of dyslipidaemia among patients using NRTI-based regimens, especially when the regimen included stavudine (D4T) [19]. The non-TDF NRTIs regimens have been shown to increase TC in the South African population on first-line ART [27]. The literatures also presented data suggesting that treatment with NRTIs-based ART (stavudine, didanosine, zidovudine or lamivudine) has been frequently associated with lipid alterations, particularly lipoatrophy and hypertriglyceridemia [3,5].…”
Section: Plos Onementioning
confidence: 99%
“…[21] A study from a South African population on ART also reported unfavorable lipid profile changes and increased CVD risk, with older age, obesity, lower CD4 count and non-tenofovir containing regimens being risk factors for elevated cholesterol. [22] Despite the increasing notion that CVD risk is raised in PLHIV, African studies looking at determinants of mortality among ART patients have not included cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection and early ART are risk factors for stroke in Malawian adults with the highest attributable risk in younger patients [ 2 ]. Individual antiretroviral drugs have also been linked to CVD through elevated markers of atherosclerosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%